2019
DOI: 10.35683/jcm18043.0022
|View full text |Cite
|
Sign up to set email alerts
|

The utilisation of performance management and development system for continuous professional development of nurse educators

Abstract: Performance management and development system (PMDS) is the collective range of future-oriented activities that focus on how individuals and groups within the organisation can continuously develop and improve their academic performances, with the overarching purpose of improving the organisation's performance. However, the South African Nursing Council (SANC) has not yet made continuous professional development (CPD) compulsory for re-registration of professional nurses. This study explores and describes the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Thus, stereotyping at the nursing college created discriminatory practices leading to the prevalence of cliques, and managers having favourites based on language, clan, or cultural background. [32] Tjale and colleagues' study [33] revealed that there was a lot of favouritism practiced in different departments at Gauteng nursing colleges, including during the implementation of nurse educators' performance management reviews. Thus, nurse educators resigned because they were frustrated that they were not treated as equals by their colleagues and managers.…”
Section: Unsupportive Management Structuresmentioning
confidence: 99%
“…Thus, stereotyping at the nursing college created discriminatory practices leading to the prevalence of cliques, and managers having favourites based on language, clan, or cultural background. [32] Tjale and colleagues' study [33] revealed that there was a lot of favouritism practiced in different departments at Gauteng nursing colleges, including during the implementation of nurse educators' performance management reviews. Thus, nurse educators resigned because they were frustrated that they were not treated as equals by their colleagues and managers.…”
Section: Unsupportive Management Structuresmentioning
confidence: 99%